Agglomeration Decrement from Nanocellulose Synthesis by adding PVA Capping Agent - Kusumawati, Endang; hidayatulloh, irwan; Elizabeth, Lidya (Jurnal Internasional Penelitian Teknologi Terapan, 2023)
Indonesia is one of the largest palm oil productions in the world. In 2017, Indonesia was responsible for almost 50% of global palm oil production. The abundant availability of Oil Palm Empty Fruit Bunches (OPEFB) has become a potential resource to be further utilized in derivative products such as cellulose, hemicellulose and lignin. The demand for nanocellulose material from extracted cellulose fibers is increasing. In this study, nanocellulose synthesis was carried out in several stages namely hydrolysis (H2SO4 64% (v/v) at 45oC for 45 minutes), delignification (NaOH 17,5% (w/v) at 80oC for 30 minutes), and bleaching (H2O2 10% (v/v) at 60oC for 15 minutes). Then, nanocellulose was subjected to ultrasonication. It was proved that nanocellulose with 50.487 nm diameters resulted from ultrasonication 50% amplitude. Moreover, adding 5%-w PVA (polyvinyl alcohol) as capping agent obtained 36.635 nm average diameter of nanocellulose. It showed nanocellulose synthesis successfully lowering agglomeration and maintaining diameter size of nano size.